Mental Health Risks Among Informal Waste Workers in Kathmandu Valley, Nepal - Alisha Karki MPH; Jiban Karki PhD; Saugat Joshi MPHGH; Michelle N. Black MPH; Barsha Rijal MScGH; Srijana Basnet BScN; Prabina Makai BScPH; Astrid Fossier Heckmann MSc; Yuba Raj Baral PhD; Andrew Lee PhD (SAGE Publishing, 2022)
Informal waste workers are a vulnerable population group who are often socio-economically marginalized and disadvantaged, with more likelihood of experiencing ill health than the general population. To explore the determinants of mental ill health in this group, we conducted a cross-sectional survey of 1278 informal waste-workers in Nepal in 2017, using a demographic health assessment questionnaire and a modified Patient Health Questionnaire (PHQ-9). We looked at the potential associations between various exposure factors and mental health outcomes and found that 27.4% of waste-workers had depressive symptoms, more likely to be reported by female (OR 2.290), older person (OR 7.757), divorced/separated (5.859), and those with ill health (OR 2.030), or disability (OR 3.562). Waste-workers with access to social protection (OR 0.538) and financial savings (OR 0.280) were less likely to have depressive symptoms. There are key risk factors that may enable identification of particularly vulnerable persons within this group and also protective factors that may help improve their mental health resilience.